2021
DOI: 10.1371/journal.pntd.0009546
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channel activation underlies transfluthrin repellency in Aedes aegypti

Abstract: Background Volatile pyrethroid insecticides, such as transfluthrin, have received increasing attention for their potent repellent activities in recent years for controlling human disease vectors. It has been long understood that pyrethroids kill insects by promoting activation and inhibiting inactivation of voltage-gated sodium channels. However, the mechanism of pyrethroid repellency remains poorly understood and controversial. Methodology/Principal findings Here, we show that transfluthrin repels Aedes aeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 52 publications
(81 reference statements)
3
21
0
Order By: Relevance
“…Repellents can be further classified by their mode of action as contact and spatial repellents depending on whether a target must contact a treated surface or react by non-tactile means to the volatilized state [29][30][31]. Active ingredients derived from synthetic pyrethroids are frequently used as spatial repellents against vectors that cover large distances, such as mosquitoes and biting flies [32,33]. The efficacy of these spatial repellents is dependent on inherent arthropod sensitivity and the ability to maintain a consistent vapor phase concentration, which is often managed with controlled release devices (CRDs) that modulate dispersion [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Repellents can be further classified by their mode of action as contact and spatial repellents depending on whether a target must contact a treated surface or react by non-tactile means to the volatilized state [29][30][31]. Active ingredients derived from synthetic pyrethroids are frequently used as spatial repellents against vectors that cover large distances, such as mosquitoes and biting flies [32,33]. The efficacy of these spatial repellents is dependent on inherent arthropod sensitivity and the ability to maintain a consistent vapor phase concentration, which is often managed with controlled release devices (CRDs) that modulate dispersion [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…aegypti adults by acting solely on the voltage-gated sodium channels. Transfluthrin-mediated repellency is a likely result of insecticide actions in selected neuronal circuits [142]. Similar repellency mediated by the activation of sodium channels has also been demonstrated for natural pyrethrins [143].…”
Section: Behavioral Insecticide Resistancementioning
confidence: 76%
“… Liu et al. (2013) have reported weak olfactory responses of Culex quinquefasciatus to permethrin and allethrin in single sensillum recordings, and a recent study with transfluthrin found no significant EAG response to this compound, with previous positive results possibility related to impurities ( Andreazza et al., 2021 ). Yang et al.…”
Section: Discussionmentioning
confidence: 94%